2022
DOI: 10.3390/cancers14246029
|View full text |Cite
|
Sign up to set email alerts
|

SETD7 Expression Is Associated with Breast Cancer Survival Outcomes for Specific Molecular Subtypes: A Systematic Analysis of Publicly Available Datasets

Abstract: SETD7 is a lysine N-methyltransferase that targets many proteins important in breast cancer (BC). However, its role and clinical significance remain unclear. Here, we used online tools and multiple public datasets to explore the predictive potential of SETD7 expression (high or low quartile) considering BC subtype, grade, stage, and therapy. We also investigated overrepresented biological processes associated with its expression using TCGA-BRCA data. SETD7 expression was highest in the Her2 (ERBB2)-enriched mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
1
1
0
Order By: Relevance
“…We showed that SETD7 expression is gradually induced when mouse MECs decrease their proliferation rate and begin to differentiate. This is concordant with the observations in human BC, where the less differentiated molecular subtype (basal-like) has lower SETD7 levels than other molecular subtypes [60].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that SETD7 expression is gradually induced when mouse MECs decrease their proliferation rate and begin to differentiate. This is concordant with the observations in human BC, where the less differentiated molecular subtype (basal-like) has lower SETD7 levels than other molecular subtypes [60].…”
Section: Discussionsupporting
confidence: 92%
“…(R)‐PFI‐2 increased cell proliferation in both mammary epithelial cell lines studied, both in undifferentiated as well as functionally differentiated stages. Although we did not carry an in‐depth investigation of the pathways that may be involved in this effect, we recently reported that human BC samples with low SETD7 mRNA expression have an overrepresentation of proteins related with the cell cycle, checkpoint, and mitosis, including CCNA2 , CDK1 , PARP1 , TTK , and VEGFA [60]. Also, other authors have shown that SETD7 inhibits several proteins important for cell cycle progression (reviewed by [2]) that can become activated by (R)‐PFI‐2.…”
Section: Discussionmentioning
confidence: 99%